Enhanced SERS performance of gold nanoparticle assemblies on a cysteine-mutant Tobacco mosaic virus scaffold - Haziq Naseer Khan; Nathaly Ortiz-Pena; Cora Moreira Da Silva; Stéphanie Lau-Truong; Guillaume Wang; Jakub Dusek; Leïla Boubekeur-Lecaque; Tomas Moravec; Damien Alloyeau; Nguyêt-Thanh Ha Duong (Journal of Science: Advanced Materials and Devices)
The employment of biomolecular templates for the synthesizing nanohybrid constructs is expanding, driven by their prospective uses in biosensing and biomedical fields. Gold nanoparticles (AuNPs) and, in particular, their assemblies are especially preferred for Surface Enhanced Raman Spectroscopy (SERS) because of their ability to amplify Raman signals through localized surface plasmon resonances, thus enabling the detection of molecules at exceedingly low concentrations. Our investigative approach is dedicated to studing the role of cysteine mutants in the nucleation and assembly of AuNPs on Tobacco mosaic virus (TMV-C, carrying T158C mutation) scaffolds. Employing biomineralization and direct grafting methods, we synthesized these nanohybrids and examined them using conventional transmission electron microscopy (TEM), in situ liquid TEM, and fluorescence spectroscopy. We demonstrated that the syntheses obtained with TMV-C give denser plasmonic nanostructures, with is ideal for SERS applications. The SERS performances of these novel nanohybrids with various AuNPs sizes and densities were evaluated, revealing excellent enhancement factors for the nanosystems obtained by direct grafting that highlight their potential for the detection of biomolecules in solution.